European experience of laparoscopic major hepatectomy. Issue 2 (February 2013) - Tzanis, Dimitrios; Shivathirthan, Nairuthya; Laurent, Alexis; Abu Hilal, Mohammad; Soubrane, Olivier; Kazaryan, Airazat M.; Ettore, Giuseppe Maria; Van Dam, Ronald M.; Lainas, Panagiotis; Tranchart, Hadrien; Edwin, Bjorn; Belli, Giulio; et al.
Abstract Background/purpose Laparoscopic hepatectomies have seen a worldwide proliferation. Major anatomic resections, which were initially considered unsuitable for laparoscopy, are currently confined to a few centers of expertise. The aim of this study was to discuss the current trends and techniques in laparoscopic major hepatectomy in Europe. Methods The prospective databases of ten European centers were combined to provide answers to a questionnaire that had been addressed to all European teams known to perform laparoscopic liver surgery. Results Between 1996 and 2011 a total of 2245 laparoscopic liver resections have been carried out, of which 495 (22 %) were major resections. The proportion of laparoscopic right and left hepatectomies varied between 4 and 40 % of all major hepatectomies of the same type. Benign, primary malignant and metastatic lesions were, respectively, 22.4, 19.6 and 58 % of all indications. The different techniques and approaches, as regards hand assistance, hepatic inflow and outflow control, liver mobilization and concomitant colectomies, are discussed. Conclusions To date, an important level of experience of laparoscopic liver resection has been accumulated in Europe, and experience of major hepatectomies is constantly increasing. However, they remain technically very demanding procedures which should be confined to expert surgeons who have already acquired considerable experience with simpler laparoscopic liver resections.